2015
DOI: 10.1051/fruits/2015042
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric characterization of peach, nectarine and plum cultivars according to fruit phenolic content and antioxidant activity

Abstract: -Introduction. Deciduous tree fruits like peach (Prunus persica (L.) Batsch var. persica), nectarine (Prunus persica (L.) Batsch var. nucipersica (Suckow) C.K.Schneid), and especialy plum (Prunus domestica L. ssp. domestica) are very common in Serbia. These fruits are known for their nutritional value and therapeutic properties and are valuable sources of antioxidants. Materials and methods. The goal of this work was to evaluate fruit tissue antioxidant activity using methanol extracts of 9 peach, 3 nectarine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
5
9
1
Order By: Relevance
“…Since flavonoids are benzo-γ-pyrone derivatives composed of polyphenolic and pyrane rings [ 56 ], the strong and positive correlation between TPC and TFC could indicate that phenolic content in stone fruits waste are composed of a high concentration of flavonoids. The similar relationship between TPC and TFC was also confirmed in the previous study [ 41 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Since flavonoids are benzo-γ-pyrone derivatives composed of polyphenolic and pyrane rings [ 56 ], the strong and positive correlation between TPC and TFC could indicate that phenolic content in stone fruits waste are composed of a high concentration of flavonoids. The similar relationship between TPC and TFC was also confirmed in the previous study [ 41 ].…”
Section: Resultssupporting
confidence: 89%
“…In terms of antioxidant assays, DPPH and ABTS were applied to determine the free radical scavenging capacity. The positive relationship between DPPH and ABTS has also been confirmed in previous study [ 41 ]. However, another antioxidant assay, FRAP, was not strongly correlated with DPPH and ABTS.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…× californica (7.9 and 9.4 mg AAE/g respectively). In total, the antioxidant potential of Chaenomeles fruits is comparable to the level shown by Mitic et al (2016) for other fruit crops, including nectarine (14.36-17.58 mg AAE/g), plum (32.43-58.30 mg AAE/g), and peach (12.31-24.55 mg AAE/g) as well as to the reducing power of Berberis fruits defined in the range 5.0-9.6 mg AAE/100 g DW (Khromykh et al, 2018).…”
Section: Discussionsupporting
confidence: 62%
“…This assumption agrees with the data of Nichols et al (2015) that the high level of phenolic compounds accumulation positively correlated with the improvement of the stability of clover plants to drought. In general, the content of phenolic compounds in the Chaenomeles fruits significantly exceeded those for some other fruit crops, including peach (0.69-4.00 mg GAE/g), nectarine (0.93-1.83 mg GAE/g), and plum (3.91-13.53 mg GAE/g), reported by Mitic et al (2016). In the fruits of different apple varieties cultivated in Italy the mean content of total polyphenols lay between 66.2 and 211.9 mg/100 g of FW (Vrhovsek et al, 2004), while other data (Wojdyło et al, 2008) showed the variation in the range from 523 to 2,724 mg GAE/100 g DW in a group of 67 different apples varieties.…”
Section: Discussionmentioning
confidence: 73%